Trends and Future Directions in Talent Management: A Systematic Literature Review and Bibliometric Analysis - Aji Kresno Murti (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This subject has undergone many changes in line with the development of the times. Therefore, this study aims to explore the latest developments by conducting a systematic literature review and bibliometric analysis of talent management based on existing empirical research. The methodology employed in this study is a systematic literature review, utilizing the term “talent management” in article titles, abstracts, and keywords from the Scopus database, yielding 13,582 publications from 2008 to 2025. The collected data will undergo bibliometric analysis using VOSviewer. Research on talent management in 2025 still largely employs classical dimensions such as attraction, recruitment, development, retention, and career management. The conceptual model of talent management has been developed in studies by incorporating digital transformation, AI capability, inclusiveness, shared leadership, organizational culture, and employee value proposition. This study utilizes the Scopus database for talent management articles. Future investigations may enhance generalizability by integrating additional databases such as the Web of Science. The implications relate to organizations’ sustainable management and development in strategies to improve the quality of human resources. This study offers analytical insights to professionals and the broader community regarding sustainable applications in work readiness for the general public.